Las representaciones expuestas a través del grafiti en Latacunga - Yánez Moreno, Mónica Patricia (2016)
This research aims to show the aesthetics of graffiti so it can be appreciated by the visual ideas of urban writers. The structure of graffiti is another important point and is based on viewer, it can generate a connotation of the represented object by the image. This cultural expression has been a topic stigmatized by the society, considering this activity as negative because its origins, it had intended to communicate disagreements to society and that is why it is associated as an expression of rebellion and vandalism often becoming an illegal activity. The results showed on this research were the dynamic art which allows urban writers through graffiti creating some concepts that present much creativity in communicating, allowing share their thoughts, meaning that arises dependent on the subject and object by graffiti, it can diffuse social and cultural issues of latacungueño context. Behind graffiti sometimes there is a story to tell based on feelings, disagreements, contributions among other things that the artist had at that time. Visual communication is the main contribution of this work, semiotics and connotation of the image is also essential to analyze in this research.